Time-harmonic response of non-homogeneous elastic unbounded domains using the scaled boundary finite-element method. - Bazyar, Mohammad Hossein
The scaled boundary finite-element method is extended to simulate time-harmonic responses of non-homogeneous unbounded domains with the elasticity modulus and mass density varying as power functions of spatial coordinates. The unbounded domains and the elasticity matrices are transformed to the scaled boundary coordinates. The scaled boundary finite-element equation in displacement amplitudes are derived directly from the governing equations of elastodynamics. To enforce the radiation condition at infinity, an asymptotic expansion of the dynamic-stiffness matrix for high frequency is developed. The dynamic-stiffness matrix at lower frequency is obtained by numerical integration of ordinary differential equations. Only the boundary is discretized yielding a reduction of the spatial dimension by one. No fundamental solution is required. Material anisotropy is modelled without additional efforts. Examples of two- and three-dimensional non-homogeneous isotropic and transversely isotropic unbounded domains are presented. The results demonstrate the accuracy and simplicity of the scaled boundary finite-element method.
Keywords: Scaled boundary finite-element method; Non-homogeneous elasticity; Dynamic stiffness; Asymptotic expansion; Unbounded domains